Time travel – a Great Method to Strengthen Cooperation between Museums and Schools. The Experience of Nationwide Time Travels in Estonia. - Kaari Siemer (EXARC Journal)
In Estonia the method of Time Travel has been used for more than 10 years. While the first time travels were conducted in a rather casual and modest way, a change took place in 2016 with the first nationwide project. By today more than 23 000 students have participated in the nationwide time travel events and it has become an important way of cooperation for museums and schools.